Bacterial Abundance In Indian White Shrimp, Penaeus Indicus Collected From Two Different Market Conditions Of Dhaka City (Dhaka University Journal of Biological Sciences, 2012)
A study was accomplished in regard to the microbiological abundance in the muscle of Indian White Shrimp (Penaeus indicus) collected from three departmental chain shops and three local markets of Dhaka metropolitan city has been assessed in terms of total bacterial count (TBC), coliform and Salmonella? Shigella (SS) counts. The TBC ranged from 2.1 ± 0.20 × 104 to 4.7 ± 0.50 × 105 cfu/g for departmental shop frozen shrimp and 4.2 ± 0.45 × 106 to 1.3 ± 0.50 × 108 cfu/g for local market iced shrimp. The total coliform count ranged between 1.6 ± 0.20 × 102 and 2.1 ± 0.25 × 103 cfu/g for the chain shop frozen shrimp and 2.8 ± 0.30 × 103 and 7.8 ± 0.50 × 105 cfu/g for the retail market iced shrimp. Furthermore, the Salmonella?Shigella (SS) count for chain shop frozen and local market iced shrimp varied from 0.5 ± 0.0 × 102 to 1.3 ± 0.10 × 102 cfu/g and 0.7 ± 0.0 × 102 to 2.1 ± 0.25 × 102 cfu/g, respectively. Presence of Vibrio spp. was confirmed in 11 samples (5 from departmental shops and 6 from local markets). In case of antibiotic sensitivity pattern of the indicator and pathogenic isolates, all of them were resistant to penicillin and bacitracin. Most of the isolates were sensitive to streptomycin, chloramphenicol and kanamycin. The results confirmed that the samples of local markets contained high pathogenic bacterial load which are supposed to be threat to food safety creating food borne diseases. DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9741 DUJBS 2012 21(1): 29-38